PENGARUH RETURN ON ASSETS (ROA),RETURN ON EQUITY(ROE), DANEARNING PER SHARE (EPS) TERHADAP HARGA SAHAM PADA PERUSAHAAN PT INDOFOOD SUKSES MAKMUR TBK YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODETAHUN 2011 –2016 (STIE Rajawali Purworejo, 2018)
This study aims to examine the effect of Return On Assets (ROA), Return on Equity (ROE), and Earning per Share (EPS) on stock prices. This research uses secondary data with research object of one company that is PT Indofood Sukses Makmur, Tbk. Analytical methods used are Multiple Linear Regression, Coefficient of Determination, Test T, and Test F.From the results of this study, through Regression Analysiscan be seen the relationship between ROA, ROE, and EPS on stock prices have a linear equation Y= 15.506 + 0.340X1 + 0.611X2 + 0.300X3. While through Determination Coefficient analysis, it can be seen that the relationship between ROA, ROE, and EPS on stock price has Adjusted R Square with negative value indicating that independent variable (ROA, ROE, and EPS) in PT Indofood Sukses Makmur atfinancial position year 2011-2016 Tbk can not be explained by the stock price(dependent variable). This happens when the value of R Square is too small because the ratio between the number of observations with the number of variables(k) is too small.So also with T test results indicating that Ho accepted Ha rejected which means partially no positive and significant influence between ROA , ROE,and EPS on stock prices. And for F test, indicating that Ho accepted Ha is rejected which means simultaneously ROA, ROE, and EPS no positive and significant influence to stock price, with the result of F arithmetic ≤ F table or 0,516 ≤ 5,79.